Fatty acid traits mediate the effects of uric acid on cancers: a Mendelian randomization study - Li, Jianing; Zhang, Yongsheng; Fu, Tong; Wang, Songyan; Cai, Hongbo; Xu, Fenghua; Xing, Guoli; Tong, Ying (Frontiers in Genetics, 2024)
IntroductionPrevious findings on the association between uric acid (UA) levels and cancer risk are conflicting. Moreover, the mechanisms underlying the interactions between UA levels, fatty acid traits, and cancer outcomes remain complex; it is still unclear whether elevated UA levels influence fatty acid traits and, thereby, contribute to an increased cancer risk. Therefore, we aimed to investigate the association between UA levels and cancer risk, with a specific focus on the potential mediating role of fatty acid traits.MethodsWe employed a Mendelian randomization (MR) analysis utilizing genetic data from large-scale genome-wide association studies to assess the causal relationships among UA levels, fatty acid traits, and cancer risk. The primary method used was the inverse variance-weighted approach alongside Bayesian-weighted Mendelian randomization. Other MR models were also applied for comparison. Sensitivity analyses, based on various statistical assumptions, were also performed to evaluate the robustness of the findings. A two-step MR analysis was conducted to explore the mediating effects of fatty acid traits on the relationship between UA levels and cancer risk.Results and Discussion Elevated UA levels were associated with an increased risk of in situ neoplasms, cervical cancer, and invasive mucinous ovarian cancer, while they were linked to a decreased risk of cancers of the eye and adnexa, small cell lung cancer, bronchus and lung cancer, respiratory system and intrathoracic organ cancers, as well as lung cancer. Mediation analysis revealed that fatty acid traits, particularly the docosahexaenoic acid/trans fatty acid ratio, mediated the relationship between UA levels and lung cancer risk. These findings underscore the potential of fatty acid traits to mediate the association between UA levels and cancer risk, offering new insights for targeted interventions and potentially improving clinical outcomes.